First record of Lutzomyia scorzai and Lutzomyia reburra (Diptera: Psychodidae) in Antioquia, Colombia - VERGARA, DANIELA; BEJARANO, EDUAR ELÍAS; CARRILLO, LINA MARÍA; SIERRA, DIANA; VÉLEZ, IVÁN DARÍO (Revista Colombiana de Entomología, 2008)
Seven species of Lutzomyia and one of Brumptomyia were collected while surveying two cutaneous leishmaniosis foci in the department Antioquia, Colombia, these are: Lutzomyia gomezi, Lu. scorzai, Lu. trapidoi, Lu. triramula, Lu. panamensis, Lu. aragaoi, Lu. reburra and Brumptomyia galindoi. Lu. scorzai (subgenus Helcocyrtomyia) and Lu. reburra (subgenus Trichophoromyia) are new records for the department. The specimens of Lu. scorzai were captured using a Shannon light trap in the municipality of Tarazá, while those of Lu. reburra were collected using CDC-like light traps near a nest of armadillo in the municipality of Urrao. The biogeographic importance of these findings is discussed given the limited distribution of both species in Colombia.